To the issue of the sustainable development of the tourism economy in the Republic of Kazakhstan - D. N. Shaikin; D. O. Abutalip; A. Zh. Bekmatova (Экономика: стратегия и практика, 2021)
The article deals with the issues of assessing the dynamics of sustainable development of the tourism economy in the Republic of Kazakhstan. Various points of view of domestic and foreign scientists and researchers to the study of the sustainable development of the tourism economy are analyzed. Based on the analysis of modern literature, the definitions are clarified and methods for assessing the dynamics of sustainable development of the tourism economy in modern conditions are supplemented. When writing the article, the authors take as a basis the state programs, including the Concept of development of the tourism industry of the Republic of Kazakhstan until 2023, the State Program of Development of the tourism industry of the Republic of Kazakhstan for 2019-2025, etc.Some statistical methods for assessing the indicators of the tourism sector are described. Using statistical data for 2015-2019, which characterize the dynamics of the number of visitors for inbound and outbound tourism, the calculations of the variation indicators, which characterize the intensity of variation of the corresponding attribute, as well as the uniformity of the composition of the studied population, are performed.